REVITALISASI TRADISI KEAGAMAAN: STUDI TRANSFORMASI MAJELIS ZIKIR BASMALAH DI KELURAHAN ABIAN TUBUH BARU - Toriq, Muhammad; Zainudin; Sukardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the transformation process of Majelis Zikir Basmalah in Abian Tubuh Baru Village and identify the supporting and inhibiting factors influencing its development. This research employed a qualitative descriptive approach with a case study design. Data were collected through observation, interviews, and documentation involving the leader of the assembly, administrators, congregation members, religious figures, and local community members. The results showed that the transformation of Majelis Zikir Basmalah occurred gradually through changes in organizational structure, religious functions, social interaction patterns, values, and adaptation to social changes. The assembly developed not only as a religious ritual forum but also as a medium for spiritual and social development within the community. Supporting factors included routine religious activities, active participation of community members, and the role of religious leaders in strengthening spirituality. Meanwhile, the primary inhibiting factor was the limited involvement of younger generations in religious activities. Overall, Majelis Zikir Basmalah plays an important role in strengthening religious values and social harmony in the community amidst modern social changes.